Friendship, love, and brotherhood in Medieval Northern Europe, c.1000-1200 - Hermanson, Lars, 1967- (Northern world, 2019)
In this book, Lars Hermanson discusses how religious beliefs and norms steered attitudes to friendship and love, and how these ways of thinking affected social identity and political behaviour. With examples taken from eleventh- and twelfth-century northern Europe, the author investigates why friendship was praised both by brotherhoods of aristocratic warriors and by brethren within monastery walls. Social and political functions rested on personal connections rather than a strong central state in the High Middle Ages. This meant that friendship was an important pragmatic instrument for establishing social order and achieving success in the game of politics